Localization Capability of Cooperative Anti-Intruder Radar Systems. (7th April 2008) - Paolini Paolini, Enrico Enrico; Giorgetti Giorgetti, Andrea Andrea; Chiani Chiani, Marco Marco; Minutolo Minutolo, Riccardo Riccardo; Montanari Montanari, Mauro Mauro
Abstract : System aspects of an anti-intruder multistatic radar based on impulse radio ultrawideband (UWB) technology are addressed. The investigated system is composed of one transmitting node and at least three receiving nodes, positioned in the surveillance area with the aim of detecting and locating a human intruder (target) that moves inside the area. Such systems, referred to also as UWB radar sensor networks, must satisfy severe power constraints worldwide imposed by, for example, the Federal Communications Commission (FCC) and by the European Commission (EC) power spectral density masks. A single transmitter-receiver pair (bistatic radar) is considered at first. Given the available transmitted power and the capability of the receiving node to resolve the UWB pulses in the time domain, the surveillance area regions where the target is detectable, and those where it is not, are obtained. Moreover, the range estimation error for the transmitter-receiver pair is discussed. By employing this analysis, a multistatic system is then considered, composed of one transmitter and three or four cooperating receivers. For this multistatic system, the impact of the nodes location on area coverage, necessary transmitted power and localization uncertainty is studied, assuming a circular surveillance area. It is highlighted how area coverage and transmitted power, on one side, and localization uncertainty, on the other side, require opposite criteria of nodes placement. Consequently, the need for a system compromising between these factors is shown. Finally, a simple and effective criterion for placing the transmitter and the receivers is drawn.